Flora and vegetation of the Natural Protected Area La Alberca, municipality of Tacámbaro, Michoacán, Mexico - Ramírez-Ramos, Fernanda; Cornejo-Tenorio, Guadalupe; Ibarra Manríquez, Guillermo (Instituto de Ecología, A.C., 2023)
Background and Aims: The Tacámbaro Alberca is one of the three crater lakes that exist in Michoacán, Mexico. The current knowledge about the flora and vegetation of this protected area is non-existent. Therefore, our objectives are to: 1) elaborate a floristic list, 2) know the degree of endemism of the flora and the species classified under some category of risk, and 3) describe the vegetation types present in La Alberca.Methods: Twenty field trips were carried out between 2018 and 2023, to collect vascular plants with reproductive structures. Taxonomic literature, comparison with type specimens, and the support of specialists for certain taxonomic groups allowed us to determine the specimens, which were deposited in the IEB, MEXU, and MO herbaria. The vegetation was described physiognomically, according to the vertical stratification, floristic composition, dominance, and foliar phenology of the tree species.Key results: A total of 450 species were determined, grouped into 287 genera and 92 families. The most diverse were Asteraceae (79 species), Fabaceae (60), Poaceae (25), Malvaceae (16) and Solanaceae (15). The genera with the highest species richness were Desmodium (12), Ipomoea (9), Solanum (8), Bletia (7), Euphorbia, Salvia, and Stevia (5 each). Herbs were the predominant growth form (70.4%). The area presents 141 (31.3%) endemic species to Mexico and 19 are included in some risk category, according to the NOM-059-SEMARNAT-2010, IUCN, and CITES. Four vegetation types are described: Pinus forest, Pinus-Quercus forest, tropical deciduous forest, and tropical subdeciduous forest.Conclusions: The Alberca de Tacámbaro has a unique floristic richness (118 species per ha). This study contributes 345 species not registered for the flora of the municipality of Tacámbaro. A new species of Nolina is recorded and Holographis peloria, Pherotrichis villosa, and Prionosciadium lilacinum are record for the first time for Michoacán.